Pendampingan Transformasi Digital Marketing Era Pandemi Covid-19 pada Peserta UMKM Jabar Juara di Kabupaten Karawang - Anggi Pasca Arnu (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The economic slowdown caused by the COVID-19 epidemic was felt in a number of critical sectors, particularly Micro, Small, and Medium bBusinesses (MSMEs), which are the backbone of the Indonesian people's economy. Characteristics of MSMEs that are still conducting business traditionally encountering difficulties and issues in coping with pandemic circumstances, and changes in customer behavior who have shifted to digital or the so-called four mega shifts in consumer behavior in covid-19. These shifts in customer behavior have an impact on the fall in turnover and even the collapse of traditional MSME enterprises. In this Abdimas, for the JABAR JUARA MSME program, carried out a way of aiding MSMEs in the pandemic period. By implementing the notion of digital transformation, we seek to increase creativity, ideas, and innovation by offering education, training, and help to MSMEs. MSMEs have undergone a transition in this service, beginning with obtaining an Business Permit Number (NIB) using the OSS application, to establishing social media profiles and market locations, to growing brand image and turnover, Understand how to utilize social media to grow your business, increase your market network, and build relationships with customers. This service activity concluded with a demonstration of MSME items at the Karawang Regency Department of Cooperatives and MSMEs.